Using virtual reality to analyze sports performance - Bideau, B.; Kulpa, R.; Vignais, N.; Brault, S.; Multon, F.; Craig, C. (IEEE Computer Graphics and Applications, 2010)
Improving performance in sports requires a better understanding of the perception-action loop employed by athletes. Because of its inherent limitations, video playback doesn`t permit this type of in-depth analysis. Interactive, immersive virtual reality can overcome these limitations and foster a better understanding of sports performance.